A digital-based education to improve occupational health and ergonomic conditions of dentists: an application of theory of planned behavior. Issue 5 (2nd September 2020) - Aliakbari, Roghieh; Vahedian-Shahroodi, Mohammad; Abusalehi, Aida; Jafari, Alireza; Tehrani, Hadi
ABSTRACT: The purpose of this study was to investigate the effect of digital education by using the Theory of Planned Behavior on the improvement of occupational health and ergonomic conditions of dentists. This Quasi-experimental study, which consisted of two descriptive and quasi-experimental parts, was conducted on 63 dentists in Bojnourd city (Iran) in 2017. The dentists were included in the study through the census method. After identifying the determinants of ergonomic conditions in the descriptive study, the Quasi-Experimental study was undertaken to determine the effect of digital intervention. Data collecting methods were demographics information questionnaire, Nordic questionnaire, a self-administered questionnaire designed in compliance with theoretical constructs and the RULA tool, which were completed before and after the intervention by dentists. More than 97% of the dentists were at high risk of developing skeletal problems. The constructs of subjective norm, perceived control, attitude and behavioral intentions were significant predictors of their ergonomic behaviors (p < 0.001). Results show that there was no significant difference in the mean attitude and knowledge scores between the experimental and control groups before the educational intervention (p = 0.164). But after the intervention, the mean attitude and knowledge scores in the experimental group were significantly different from before the intervention (p < .05). Training based on the (TBP) using digital media was effective in the knowledge and attitude of ergonomic conditions of the dentists. However, it was not effective for behavioral intention.